Advanced engineering fluid mechanics / K. Muralidhar, Gautam Biswas - Muralidhar, K. (Alpha Science International, 2005)
Fluid mechanics continues to dominate the world of engineering. This book bridges the gap between first and higher level text books on the subject. It shows that the approximate approaches are essentially globally averaged versions of the local treatment, that in turn is covered in considerable detail in the second edition.